2015
DOI: 10.18488/journal.88/2015.1.1/88.1.1.12
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Selected Financial Ratios on Profitability: An Empirical Analysis of Listed Firms of Cement Sector in Saudi Arabia

Abstract: The plinth emergence of infrastructures sector in the Kingdom of Saudi Debtors' Turnover Ratio (DTR), Creditors' Velocity (CRSV), Total Assets Turnover Ratio (TATR) and Net profit Margin (NPM). Profitability as a dependent variable is exhibited by Net profit Margin (NPM) while the selected ratios DER, ITR, DTR, CRSV, TATR and CRSV are expressed as independent variables. Based on the findings of the study, it is cogently revealed that there is a significant relationship between the three selected ratios and Net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Al-Zoubi (2015) conducted a fundamental analysis of Saudi Cement Industry over a period of five years from 2010 to 2014 and found that Operating Profit and Net Profit of the Saudi Cement Companies does not differ significantly. Khan & Khokhar (2015) studied the effect of financial ratios on profitability of listed firms of cement sector in Saudi Arabia over a period of 5 years from 2008 to 2012. Das & Mal (2016) conducted a research on profitability of twelve cement companies in India during a period of ten years from 2001 to 2010.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Al-Zoubi (2015) conducted a fundamental analysis of Saudi Cement Industry over a period of five years from 2010 to 2014 and found that Operating Profit and Net Profit of the Saudi Cement Companies does not differ significantly. Khan & Khokhar (2015) studied the effect of financial ratios on profitability of listed firms of cement sector in Saudi Arabia over a period of 5 years from 2008 to 2012. Das & Mal (2016) conducted a research on profitability of twelve cement companies in India during a period of ten years from 2001 to 2010.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The result came that default determinants were Working Capital to Total Assets, Current Ratio, Book value of equity to total liabilities, Total Debt to Total Assets, EBIT to Current Liabilities, and Institutional Ownership (Dewi & Hadri, 2017). Khan and Khokhar (2015) did a research to find out the profitability of listed cement companies of Kingdom of Saudi Arabia (KSA) from 2008-12. The results reveal that Debt to Equity Ratio (Baltaev,#21), Inventory Turnover Ratio (ITR) and Creditors' Velocity (CRSV) have positive relationship with profitability of the companies.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Direct effects of sectors, as well as financial statements, on stock performance have been extensively studied in literature. See for instance Fama & French (1993); Graham et al (2002); Callen & Segal (2004); Edirisinghe & Zhang (2008); Dimitropoulos & Asteriou (2009); Fama & French (2015); Khan & Khokhar (2015); Enke & Thawornwong (2005); Huang et al (2019). Yet as to be evidently shown by the empirical analysis in section 3.2, the companies' belonging sectors also significantly affect stock returns indirectly through certain financial metrics in the statements.…”
Section: Introductionmentioning
confidence: 96%